Early parental deprivation in the marmoset monkey produces long-term changes in hippocampal expression of genes involved in synaptic plasticity and implicated in mood disorder. - Law, A; Pei, Q; Walker, M; Gordon-Andrews, H; Weickert, C; Feldon, J; Pryce, C; Harrison, P (2009)
In mood disorder, early stressors including parental separation are vulnerability factors, and hippocampal involvement is prominent. In common marmoset monkeys, daily parental deprivation during infancy produces a prodepressive state of increased basal activity and reactivity in stress systems and mild anhedonia that persists at least to adolescence. Here we examined the expression of eight genes, each implicated in neural plasticity and in the pathophysiology of mood disorder, in the hippocampus of these same adolescent marmosets, relative to their normally reared sibling controls. We also measured hippocampal volume. Early deprivation led to decreases in hippocampal growth-associated protein-43 (GAP-43) mRNA, serotonin 1A receptor (5-HT(1A)R) mRNA and binding ([3H]WAY100635), and to increased vesicular GABA transporter mRNA. Brain-derived neurotrophic factor (BDNF), synaptophysin, vesicular glutamate transporter 1 (VGluT1), microtubule-associated protein-2, and spinophilin transcripts were unchanged. There were some correlations with in vivo biochemical and behavioral indices, including VGluT1 mRNA with reward-seeking behavior, and serotonin 1A receptor mRNA with CSF cortisol. Early deprivation did not affect hippocampal volume. We conclude that early deprivation in a nonhuman primate, in the absence of subsequent stressors, has a long-term effect on the hippocampal expression of genes implicated in synaptic function and plasticity. The reductions in GAP-43 and serotonin 1A receptor expressions are comparable with findings in mood disorder, supporting the possibility that the latter reflect an early developmental contribution to disease vulnerability. Equally, the negative results suggest that other features of mood disorder, such as decreased hippocampal volume and BDNF expression, are related to different aspects of the pathophysiological process.